Paraneoplastic pemphigus and reported, identified underlying diseases - Iwańczuk, Paweł (Journal of Education, Health and Sport, 2024)
Introduction: Pemphigus is a rare group of autoimmune diseases that promote development of various skin eruptions, the most commonly it presents with blisters. The several types of pemphigus are: pemphigus vulgaris, pemphigus foliaceus, intraepidermal neutrophillic IgA dermatosis and especially rare type- paraneoplastic pemphigus, which is main topic of this publication. Paraneoplastic pemphigus is a disease which affects patients with developing carcinogenesis process. Usually it is a malignant process, but there are also some cases which describe paraneoplastic pemphigus associated with benign tumors. Because of its occurence our current level of knowledge about different aspects of paraneoplastic pemphigus is not final and as comprehensive as researchers and patients wish. Aim of study: The main purpose of this publication is presentation a review of literature about paraneoplastic pemphigus- its epidemiology, physiopathology, pathomorfology, clinical features, and description of different types of benign or malignant processes which concomitence with paraneoplastic pemphigus. State of knowledge: Paraneoplastic pemphigus is a rare autoimmune disease, which aspects are not widely described, but there are some reports about epidemiology, pathophysiology, histopathology, treatment and associated confirmed malignancies. The challenge for future is to formulate clear, formal, treatment protocols for paraneoplastic pemphigus. Conclusion: Paraneoplastic pemphigus is a very fascinating disease for researchers because there are still very limited reports and statistics about this very rare disorder. Nonetheless year by year our level of knowledge about pathogenesis, clinical features, associated malignant and benign processes is growing and it can affect more personalized, effective treatment methods and protocoles.